Factors influencing consumer ethical decision making of purchasing pirated software: structural equation modelling on Malaysian consumer - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Khatibi, Ali (American Scholars Press, 2010)
The study explores the factors influencing consumer ethical decision making when purchasing pirated software. 300 questionnaires were distributed among potential respondents for this study, of which 250 were returned.After completing the screening process, only 200 responses were considered complete and valid to undergo data analysis. In this study, exploratory factor analysis was used to identify the salient attributes that impact consumer ethical decision making when purchasing pirated software. In addition, SEM (Structural Educational Modeling) was employed to identify the relationship among the variables. The results of the study showed that there is a significant relationship between consumer moralities, social influence, and consumer moral judgment towards the consumer ethical decision-making when purchasing pirated software. The outcome of this research showed a comprehensively integrated framework allowing policy makers and business enterprises to explore dimensions like morality, social influences and moral judgment and their effect on the consumer’s decision-making in purchasing pirated software. However, further research is needed to examine these factors in Malaysia with additional samples before generalizations can be accurately made.